Perspective on the use of methanogens in lithium recovery from brines - Abdel Azim, Annalisa; Vizzarro, Arianna; Bellini, Ruggero; Bassani, Ilaria; Baudino, Luisa; Pirri, Candido Fabrizio; Verga, Francesca; Lamberti, Andrea; Menin, Barbara (Frontiers in Microbiology, 2023)
Methanogenic archaea stand out as multipurpose biocatalysts for different applications in wide-ranging industrial sectors due to their crucial role in the methane (CH4) cycle and ubiquity in natural environments. The increasing demand for raw materials required by the manufacturing sector (i.e., metals-, concrete-, chemicals-, plastic- and lubricants-based industries) represents a milestone for the global economy and one of the main sources of CO2 emissions. Recovery of critical raw materials (CRMs) from byproducts generated along their supply chain, rather than massive mining operations for mineral extraction and metal smelting, represents a sustainable choice. Demand for lithium (Li), included among CRMs in 2023, grew by 17.1% in the last decades, mostly due to its application in rechargeable lithium-ion batteries. In addition to mineral deposits, the natural resources of Li comprise water, ranging from low Li concentrations (seawater and freshwater) to higher ones (salt lakes and artificial brines). Brines from water desalination can be high in Li content which can be recovered. However, biological brine treatment is not a popular methodology. The methanogenic community has already demonstrated its ability to recover several CRMs which are not essential to their metabolism. Here, we attempt to interconnect the well-established biomethanation process with Li recovery from brines, by analyzing the methanogenic species which may be suitable to grow in brine-like environments and the corresponding mechanism of recovery. Moreover, key factors which should be considered to establish the techno-economic feasibility of this process are here discussed.